Life among the savages - Jackson, Shirley, 1916-1965. (New York : Penguin, 1997)
American author Shirley Jackson's memoir of everyday life with her husband and two children in Vermont.
Adult
Keywords: Jackson, Shirley, -- 1916-1965.; Jackson, Shirley, -- 1916-1965.; Authors, American -- 20th century -- Biography; American authors -- Biography; Women -- Biography